Моби Дик, или Белый Кит: роман / Герман Мелвилл - Мелвилл Герман (Азбука-классика, 2007)
Экземпляры: ф.17 (ретро) / Инвентарный номер: 46139 / Цена: / Сис.шифр: Ш6(7Сое) / Авт.знак: М 479 / ГРНТИ: 17.82.31 / ББК: Ш6(7Сое)